2019
DOI: 10.1016/j.mex.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-comfort-data: A method to collect comprehensive information on thermal comfort in school classrooms

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Some studies showed that the standards have limited suitability in environments such as educational buildings, as they were developed based mainly on adult subjects working in offices. Therefore, alternative methods such as the one proposed in [24,65] are needed for comprehensive data gathering within different contexts.…”
Section: Main Findings From the Published Documentsmentioning
confidence: 99%
“…Some studies showed that the standards have limited suitability in environments such as educational buildings, as they were developed based mainly on adult subjects working in offices. Therefore, alternative methods such as the one proposed in [24,65] are needed for comprehensive data gathering within different contexts.…”
Section: Main Findings From the Published Documentsmentioning
confidence: 99%
“…To solve this distance, more fieldwork should be performed before methods are included in standards [63]. This proposal from 2002 remains open, with subsequent research confirming the need to improve the procedures defined by the standards [64] Field studies on thermal comfort confirm that personal understanding conditions the evaluation, and the results can vary depending on context and time. This situation confirms the changing relation between people, climate, and buildings posited by some authors [65].…”
Section: Bibliography Analysismentioning
confidence: 99%
“…Consequently, indoor air quality in schools has a strong impact on children's exposure to air pollutants and can also influence their learning capacities (Mendell and Heath, 2005;Simoni et al, 2010). Indoor air quality in schools is usually characterized by a range of parameters including temperature, relative humidity, and levels of carbon dioxide (CO2), ventilation rates and average concentrations of gaseous pollutants (Gaihre et al, 2014;Jiang et al, 2018;Rodriguez et al, 2019;Verriele et al, 2016) although there is no specific guidelines to assess IAQ in classrooms. These latter are usually determined by a single measurement over 4.5 or 7 days of passive sampling.…”
Section: Introductionmentioning
confidence: 99%